Impacts of Weather Types on Soil Erosion Rates in Vineyards at “Celler Del Roure” Experimental Research in Eastern Spain. - Rodrigo-Comino, Jesús; Senciales-González, José María; Terol, Enric; Mora-Navarro, Gaspar; Gyasi-Agyei, Yeboah; Cerdà-Bolinches, Artemio (MDPI, 2020)
To understand soil erosion processes, it is vital to know how the weather types and atmospheric situations, and their distribution throughout the year, affect the soil erosion rates. This will allow for the development of efficient land management practices to mitigate water-induced soil losses. Vineyards are one of the cultivated areas susceptible to high soil erosion rates. However, there is a lack of studies that link weather types and atmospheric conditions to soil erosion responses in viticultural areas. Thus, the main aim of this research is to assess the impacts of weather types and atmospheric conditions on soil erosion processes in a conventional vineyard with tillage in eastern Spain. To achieve this goal, rainfall events from 2006 to 2017 were monitored and the associated runoff and soil loss were collected from experimental plots. Our results showed that the highest volume of runoff and soil erosion is linked to rainfall associated with the eastern winds that accounted for 59.7% of runoff and 63.9% of soil loss, while cold drops in the atmospheric situation classifications emerged as the highest contributor of 40.9% in runoff and 44.1% in soil loss. This paper provides new insights into the development of soil erosion control measures that help to mitigate the negative impact of extreme rainfall and runoff considering atmospheric conditions.
Keywords: Suelos - Erosión; Escorrentía; Climatología; Precipitaciones atmosféricas; Viñedos - Suelos; Soil loss; Runoff; Weather types; Vineyards; Cold drops